Iron-based amorphous nanocrystalline alloy and preparation method thereof
By optimizing the element composition in iron-based amorphous nanocrystalline alloys, especially replacing Si with P and optimizing the content of Cu and Nb, and partially replacing Fe with Co, the problem of difficulty in achieving high saturation magnetic induction strength and low coercivity at the same time, the high performance and suitable miniaturization requirements of the alloy are achieved.
Patent Information
- Application Number
- CN202411748714.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
Smart Images

Figure CN119553190A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic materials, and in particular to an Fe-based amorphous nanocrystalline soft magnetic alloy material and a preparation method thereof. Background Art
[0002] Soft magnetic materials are responsible for the generation and conversion of energy in various electromagnetic devices and motor-powered machines, and are crucial in the electrified world. At present, iron-based amorphous alloys have been widely used in magnetic electronic components such as mutual inductors, common-mode inductors, inverters, and high-frequency alternating magnetic field environments such as motors and transformers. In view of the global energy crisis and the strict requirements of emission reduction, modern electronic products (such as motors and generators) are developing in the direction of high frequency, miniaturization and high efficiency, and it is necessary to develop iron-based amorphous nanocrystalline alloys with both high saturation magnetic induction intensity (Bs) and low coercive force (Hc). However, it is difficult to achieve both high Bs and low Hc in traditional iron-based amorphous nanocrystalline alloys.
[0003] For Fe-based amorphous nanocrystalline alloys, Bs is basically related to the content of ferromagnetic elements and their crystal phase volume fraction. In order to increase Bs, it is necessary to increase the content of ferromagnetic elements as much as possible. However, increasing the content of ferromagnetic elements at the expense of reducing non-ferromagnetic elements will lead to various problems, such as a decrease in amorphous forming ability (AFA), a narrowing of the crystallization temperature window, and thus abnormal growth of nanocrystals and degradation of soft magnetic properties (SMP). Therefore, how to balance the relationship between Bs and AFA-SMP is a fundamental problem that needs to be solved for Fe-based amorphous nanocrystalline alloys. Summary of the invention
[0004] Based on this, the present application provides an iron-based amorphous nanocrystalline alloy and a preparation method thereof. The preparation method of the iron-based amorphous nanocrystalline alloy of the present application can make the prepared iron-based amorphous nanocrystalline alloy not only have higher saturation magnetic induction intensity and lower coercivity, but also have better amorphous forming ability and wider annealing temperature window.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides an iron-based amorphous nanocrystalline alloy having the chemical formula: Fe 85-x Co x B 14- y P y Cu 0.5 Nb 0.5 , where 0≤x≤10,4≤y≤10.
[0007] The present invention is based on the Fe 73.5 Si 13.5B9Cu1Nb3 nanocrystalline alloy, by replacing Si with P to control the atomic size mismatch and mixing enthalpy of the alloy, while optimizing the content of Cu and Nb elements, to increase the amorphous forming ability of the system, thereby increasing the content of ferromagnetic elements and improving Bs. Then, by partially replacing Fe with Co, the amorphous forming ability of the alloy system is increased and Bs is increased. The above-mentioned various alloying elements work synergistically, and the resulting iron-based amorphous nanocrystalline soft magnetic alloy is characterized by low cost, high amorphous forming ability and a wide heat treatment process window, and also has high saturation magnetic induction intensity and low coercive force.
[0008] In a second aspect, the present invention provides a method for preparing an iron-based amorphous nanocrystalline alloy. According to a specific embodiment of the present invention, the method comprises the following steps:
[0009] Step 1: Prepare raw materials
[0010] High-purity iron, pure cobalt, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio; during the placing process, a layer of iron particle raw material is first spread on the bottom of the crucible and then other raw materials are placed in sequence, and finally another layer of iron particle raw material is spread to prevent the volatilization of the P element.
[0011] Step 2: Vacuum
[0012] Place the ceramic crucible in the heating coil, close the furnace door, and pre-evacuate the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3 Pa, then turn off the diffusion pump and inject high-purity argon gas with a pressure of 0.05MPa to form a protective gas atmosphere.
[0013] Step 3: Melting alloy ingots
[0014] During smelting, first adjust the current to 400A, then increase it by 50A and keep it warm for 2 minutes, then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times. After keeping the molten alloy liquid in a bright red state for 10 minutes, reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0015] Step 4: Preparation of amorphous ribbon
[0016] The alloy ingot obtained in step 3 is used to remove the surface oxide layer using a grinder, and then is crushed using a vise. The surface dust and attached oil stains caused by the crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube;
[0017] Put the quartz tube containing the alloy ingot into the heating coil of the belt-spinning machine, close the furnace door, purge with high-purity argon gas three times, evacuate to below 10Pa with a mechanical pump, and then flush with high-purity argon gas to form a protective atmosphere to prevent oxidation. At the same time, adjust the pressure difference to 0.03Mpa, heat the alloy ingot to a molten state, and quickly spray it onto a copper roller with a rotation speed of 40m / s. Using the high thermal conductivity of copper, the metal melt is cooled faster than the critical cooling rate to form an amorphous strip. In order to reduce errors, the same alloy composition is used to prepare strips with the same test tube.
[0018] Step 5: Annealing of amorphous strip
[0019] Cut the amorphous strip obtained in step 4 into 70mm pieces and place them in a porcelain boat; place the porcelain boat in the non-heating zone of the tubular furnace, evacuate the tubular furnace and then introduce nitrogen, repeat 5 times, and finally maintain a circulating nitrogen atmosphere in the tubular furnace; heat the tubular furnace to a preset temperature, which is 600℃~900℃; push the porcelain boat into the heating zone of the tubular furnace and keep it warm at the preset temperature for different time periods, and the keeping time is 10s~80s; then quickly push the porcelain boat back to the unheated zone for cooling; the non-heating zone is at least 1m away from the heating zone.
[0020] In step 1, the purity of high-purity iron is 99.95%, the purity of pure copper is 99.999%, the purity of pure niobium is 99.95%, and the purity of pure boron is 99.9%.
[0021] The purity of the Fe-P master alloy is (99.9%), wherein the content of Fe is 76.57wt.%, and the content of P is 23.43wt.%.
[0022] In step 4, the dimensions of the iron-based amorphous alloy strip are generally: a width of 1 to 1.5 mm and a thickness of 20 to 30 um.
[0023] In step five, the obtained iron-based amorphous nanocrystalline alloy has a saturation magnetic induction intensity of 1.76T to 1.86T and a coercive force of 1.6A / m to 5.2A / m.
[0024] In the above-mentioned preparation method of the iron-based amorphous nanocrystalline alloy, the amorphous strip is placed in a porcelain boat, and the porcelain boat is placed in the non-heating zone of the tubular furnace. In a nitrogen atmosphere, when the heating furnace is heated to a predetermined temperature, the porcelain boat is pushed into the heating zone of the tubular furnace, and kept at a preset temperature for a predetermined time, and then the porcelain boat is quickly pushed back to the non-heating zone for cooling. This method can achieve high-temperature rapid annealing in a nitrogen atmosphere without the need for an embedding medium, and can also avoid the rapid growth of nanocrystals precipitated in the iron-based amorphous alloy matrix and the oxidation of the strip during traditional long-term annealing, thereby avoiding the deterioration of soft magnetic properties.
[0025] The preparation method of the iron-based amorphous nanocrystalline alloy of the present application can make the prepared iron-based amorphous nanocrystalline alloy not only have good amorphous forming ability and a wide annealing temperature window, but also have high saturation magnetic induction intensity and low coercive force, which can more effectively meet the needs of miniaturization of electrical components and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD curve image of the iron-based amorphous strip prepared in Example 1-5;
[0027] Figure 2 The DSC curve images of the iron-based amorphous strips prepared in Examples 1-5;
[0028] Figure 3 BH curve diagram of the iron-based amorphous nanocrystalline alloy provided in Examples 1-5 of the present application;
[0029] Figure 4 It is a curve diagram of Hc and Bs changes under optimal annealing conditions for Examples 1-5 and Comparative Examples 1-5 of the present application. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below by means of specific implementation methods. The following definitions are only for better illustrating the technical solution of the present invention and should not be regarded as further limitations of the technical solution.
[0031] Example 1
[0032] This embodiment provides an iron-based amorphous nanocrystalline alloy, whose chemical formula is: Fe 85 B5P9Cu 0.5 Nb 0.5 , that is, the atomic percentage of each alloy element is: Fe 85at%, B 5at%, P 9at%, Cu 0.5at%, Nb 0.5at%.
[0033] The method for preparing the above-mentioned iron-based amorphous nanocrystalline alloy comprises the following steps:
[0034] (1) High-purity iron, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio; during the placement process, a layer of iron particle raw material is first placed on the bottom of the crucible, and then other raw materials are placed in sequence, and finally another layer of iron particle raw material is placed to prevent the volatilization of the P element.
[0035] (2) Vacuuming: Place the ceramic crucible in the heating coil, close the furnace door, and pre-vacuum the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, turn off the mechanical pump and use the diffusion pump to evacuate to 5×10 -3Pa, then turn off the diffusion pump and flush in high-purity argon gas with a pressure of 0.05MPa.
[0036] (3) Using the induction melting method, first adjust the current to 400A, then increase it by 50A for 2 minutes, and then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times, and keep the molten alloy liquid in a bright red state for 10 minutes. Then reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0037] (4) The obtained alloy ingot is used to remove the surface oxide layer with a grinding wheel, and then crushed with a vise. The surface dust and attached oil stains caused by crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube, and then the quartz tube is placed in the heating coil of the belt-spinning machine. The furnace door is closed and the gas is washed with high-purity argon gas for 3 times. When the cavity is pre-evacuated to below 10Pa with a mechanical pump, high-purity argon gas is then injected to form a protective atmosphere to prevent oxidation. The rotation speed of the copper roller is set to 40m / s, and the pressure difference of the spray casting is set to 0.03MPa. The alloy ingot designed to be distributed is fully melted, and then the molten master alloy liquid is sprayed on the surface of the high-speed rotating copper roller using the pre-set argon pressure difference. The high-speed rotating water-cooled copper roller has a rapid cooling ability, which makes the molten alloy liquid solidify instantly, and an amorphous alloy strip with a width of 1 to 1.5mm and a thickness of 20 to 30um is prepared.
[0038] (5) Cut the amorphous strip into 70 mm pieces and place them in a porcelain boat, place the porcelain boat in a non-heating zone of a tubular furnace, evacuate the tubular furnace, and then introduce nitrogen, repeat this process 5 times, and finally maintain a circulating nitrogen atmosphere in the tubular furnace. When the tubular furnace is heated to a predetermined temperature, push the porcelain boat into the heating zone of the tubular furnace and keep it warm for a predetermined time. In this embodiment, multiple experimental groups are repeated. When the preset temperature is 600° C., the temperature is kept warm for 60s, 65s, 70s, 75s, and 80s, respectively; when the preset temperature is 650° C., the temperature is kept warm for 50s, 55s, 60s, 65s, and 80s, respectively. When the preset temperature is 700℃, keep warm for 30s, 35s, 40s, 45s, and 50s respectively; when the preset temperature is 750℃, keep warm for 20s, 25s, 30s, 35s, and 40s respectively; when the preset temperature is 800℃, keep warm for 15s, 20s, 25s, 30s, and 35s respectively; when the preset temperature is 850℃, keep warm for 10s, 15s, 20s, and 25s respectively; when the preset temperature is 900℃, keep warm for 10s, 15s, 20s, and 25s respectively; after keeping warm, quickly push the porcelain boat back to the non-heating area for cooling, and the iron-based amorphous nanocrystalline alloy Fe 85 B5P9Cu 0.5 Nb 0.5 .
[0039] Example 2
[0040] This embodiment provides an iron-based amorphous nanocrystalline alloy, whose chemical formula is: Fe 85 B7P7 0.5 Nb 0.5 , that is, the atomic percentage of each alloy element is: Fe85at%, B7at%, P7at%, Cu0.5at%, Nb0.5at%.
[0041] The method for preparing the above-mentioned iron-based amorphous nanocrystalline alloy comprises the following steps:
[0042] (1) High-purity iron, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio. During the placement process, a layer of iron particle raw materials is first placed on the bottom of the crucible, and then other raw materials are placed in sequence, and finally another layer of iron particle raw materials is placed to prevent the volatilization of the P element.
[0043] (2) Vacuuming: Place the ceramic crucible in the heating coil, close the furnace door, and pre-vacuum the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3 Pa, then turn off the diffusion pump and flush in high-purity argon gas with a pressure of 0.05MPa.
[0044] (3) Using the induction melting method, first adjust the current to 400A, then increase it by 50A for 2 minutes, and then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times, and keep the molten alloy liquid in a bright red state for 10 minutes. Then reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0045] (4) The obtained alloy ingot is used to remove the surface oxide layer with a grinding wheel, and then crushed with a vise. The surface dust and attached oil stains caused by crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube, and then the quartz tube is placed in the heating coil of the belt-spinning machine. The furnace door is closed and the gas is washed with high-purity argon gas for 3 times. When the cavity is pre-evacuated to below 10Pa with a mechanical pump, high-purity argon gas is then injected to form a protective atmosphere to prevent oxidation. The rotation speed of the copper roller is set to 40m / s, and the pressure difference of the spray casting is set to 0.03MPa. The alloy ingot designed to be distributed is fully melted, and then the molten master alloy liquid is sprayed on the surface of the high-speed rotating copper roller using the pre-set argon pressure difference. The high-speed rotating water-cooled copper roller has a rapid cooling ability, which makes the molten alloy liquid solidify instantly, and an amorphous alloy strip with a width of 1 to 1.5mm and a thickness of 20 to 30um is prepared.
[0046] (5) Cut the amorphous strip into 70 mm pieces and place them in a porcelain boat, place the porcelain boat in a non-heating zone of a tubular furnace, evacuate the tubular furnace, and then introduce nitrogen, repeat this process 5 times, and finally maintain a circulating nitrogen atmosphere in the tubular furnace. When the tubular furnace is heated to a predetermined temperature, push the porcelain boat into the heating zone of the tubular furnace and keep it warm for a predetermined time. In this embodiment, multiple experimental groups are repeated. When the preset temperature is 600° C., the temperature is kept warm for 60s, 65s, 70s, 75s, and 80s, respectively; when the preset temperature is 650° C., the temperature is kept warm for 50s, 55s, 60s, 65s, and 80s, respectively. When the preset temperature is 700℃, keep warm for 30s, 35s, 40s, 45s, and 50s respectively; when the preset temperature is 750℃, keep warm for 20s, 25s, 30s, 35s, and 40s respectively; when the preset temperature is 800℃, keep warm for 15s, 20s, 25s, 30s, and 35s respectively; when the preset temperature is 850℃, keep warm for 10s, 15s, 20s, and 25s respectively; when the preset temperature is 900℃, keep warm for 10s, 15s, 20s, and 25s respectively; after keeping warm, quickly push the porcelain boat back to the non-heating area for cooling, and the iron-based amorphous nanocrystalline alloy Fe 85 B7P7 0.5 Nb 0.5 .
[0047] Example 3
[0048] This embodiment provides an iron-based amorphous nanocrystalline alloy, whose chemical formula is: Fe 85 B9P5Cu 0.5 Nb 0.5 , that is, the atomic percentage of each alloy element is: Fe85at%, B9at%, P5at%, Cu0.5at%, Nb0.5at%.
[0049] The method for preparing the above-mentioned iron-based amorphous nanocrystalline alloy comprises the following steps:
[0050] (1) High-purity iron, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio. During the placement process, a layer of iron particle raw materials is first placed on the bottom of the crucible, and then other raw materials are placed in sequence, and finally another layer of iron particle raw materials is placed to prevent the volatilization of the P element.
[0051] (2) Vacuuming: Place the ceramic crucible in the heating coil, close the furnace door, and pre-vacuum the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3 Pa, then turn off the diffusion pump and inject high-purity argon gas with a pressure of 0.05MPa.
[0052] (3) Using the induction melting method, first adjust the current to 400A, then increase it by 50A for 2 minutes, and then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times, and keep the molten alloy liquid in a bright red state for 10 minutes. Then reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0053] (4) The obtained alloy ingot is used to remove the surface oxide layer with a grinding wheel, and then crushed with a vise. The surface dust and attached oil stains caused by crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube, and then the quartz tube is placed in the heating coil of the belt-spinning machine. The furnace door is closed and the gas is washed with high-purity argon gas for 3 times. When the cavity is pre-evacuated to below 10Pa with a mechanical pump, high-purity argon gas is then injected to form a protective atmosphere to prevent oxidation. The rotation speed of the copper roller is set to 40m / s, and the pressure difference of the spray casting is set to 0.03MPa. The alloy ingot designed to be distributed is fully melted, and then the molten master alloy liquid is sprayed on the surface of the high-speed rotating copper roller using the pre-set argon pressure difference. The high-speed rotating water-cooled copper roller has a rapid cooling ability, which makes the molten alloy liquid solidify instantly, and prepares an amorphous alloy strip with a width of 1 to 1.5mm and a thickness of 20 to 30um.
[0054] (5) Cut the amorphous strip into 70 mm pieces and place them in a porcelain boat, place the porcelain boat in a non-heating zone of a tubular furnace, evacuate the tubular furnace, and then introduce nitrogen, repeat this process 5 times, and finally maintain a circulating nitrogen atmosphere in the tubular furnace. When the tubular furnace is heated to a predetermined temperature, push the porcelain boat into the heating zone of the tubular furnace and keep it warm for a predetermined time. In this embodiment, multiple experimental groups are repeated. When the preset temperature is 600° C., the temperature is kept warm for 60s, 65s, 70s, 75s, and 80s, respectively; when the preset temperature is 650° C., the temperature is kept warm for 50s, 55s, 60s, 65s, and 80s, respectively. When the preset temperature is 700℃, keep warm for 30s, 35s, 40s, 45s, and 50s respectively; when the preset temperature is 750℃, keep warm for 20s, 25s, 30s, 35s, and 40s respectively; when the preset temperature is 800℃, keep warm for 15s, 20s, 25s, 30s, and 35s respectively; when the preset temperature is 850℃, keep warm for 10s, 15s, 20s, and 25s respectively; when the preset temperature is 900℃, keep warm for 10s, 15s, 20s, and 25s respectively; after keeping warm, quickly push the porcelain boat back to the non-heating area for cooling, and the iron-based amorphous nanocrystalline alloy Fe 85 B9P5Cu 0.5 Nb 0.5 .
[0055] Example 4
[0056] This embodiment provides an iron-based amorphous nanocrystalline alloy, whose chemical formula is: Fe 80 Co5B9P5Cu 0.5 Nb 0.5 , that is, the atomic percentage of each alloy element is: Fe80at%, Co5at%, B9at%, P5at%, Cu0.5at%, Nb0.5at%.
[0057] The method for preparing the above-mentioned iron-based amorphous nanocrystalline alloy comprises the following steps:
[0058] (1) High-purity iron, pure cobalt, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio; during the placement process, a layer of iron particle raw material is first placed on the bottom of the crucible, and then other raw materials are placed in sequence, and finally another layer of iron particle raw material is placed to prevent the volatilization of the P element.
[0059] (2) Vacuuming: Place the ceramic crucible in the heating coil, close the furnace door, and pre-vacuum the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3Pa, then turn off the diffusion pump and flush in high-purity argon gas with a pressure of 0.05MPa.
[0060] (3) Using the induction melting method, first adjust the current to 400A, then increase it by 50A for 2 minutes, and then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times, and keep the molten alloy liquid in a bright red state for 10 minutes. Then reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0061] (4) The obtained alloy ingot is used to remove the surface oxide layer with a grinding wheel, and then crushed with a vise. The surface dust and attached oil stains caused by crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube, and then the quartz tube is placed in the heating coil of the belt-spinning machine. The furnace door is closed and the gas is washed with high-purity argon gas for 3 times. When the cavity is pre-evacuated to below 10Pa with a mechanical pump, high-purity argon gas is then injected to form a protective atmosphere to prevent oxidation. The rotation speed of the copper roller is set to 40m / s, and the pressure difference of the spray casting is set to 0.03MPa. The alloy ingot designed to be distributed is fully melted, and then the molten master alloy liquid is sprayed on the surface of the high-speed rotating copper roller using the pre-set argon pressure difference. The high-speed rotating water-cooled copper roller has a rapid cooling ability, which makes the molten alloy liquid solidify instantly, and an amorphous alloy strip with a width of 1 to 1.5mm and a thickness of 20 to 30um is prepared.
[0062] (5) Cut the amorphous strip into 70 mm pieces and place them in a porcelain boat, place the porcelain boat in a non-heating zone of a tubular furnace, evacuate the tubular furnace, and then introduce nitrogen, repeat this process 5 times, and finally maintain a circulating nitrogen atmosphere in the tubular furnace. When the tubular furnace is heated to a predetermined temperature, push the porcelain boat into the heating zone of the tubular furnace and keep it warm for a predetermined time. In this embodiment, multiple experimental groups are repeated. When the preset temperature is 600° C., the temperature is kept warm for 60s, 65s, 70s, 75s, and 80s, respectively; when the preset temperature is 650° C., the temperature is kept warm for 50s, 55s, 60s, 65s, and 80s, respectively. When the preset temperature is 700℃, keep warm for 30s, 35s, 40s, 45s, and 50s respectively; when the preset temperature is 750℃, keep warm for 20s, 25s, 30s, 35s, and 40s respectively; when the preset temperature is 800℃, keep warm for 15s, 20s, 25s, 30s, and 35s respectively; when the preset temperature is 850℃, keep warm for 10s, 15s, 20s, and 25s respectively; when the preset temperature is 900℃, keep warm for 10s, 15s, 20s, and 25s respectively; after keeping warm, quickly push the porcelain boat back to the non-heating area for cooling, and the iron-based amorphous nanocrystalline alloy Fe 80 Co5B9P5Cu 0.5 Nb 0.5.
[0063] Example 5
[0064] This embodiment provides an iron-based amorphous nanocrystalline alloy, whose chemical formula is: Fe 75 Co 10 B9P5Cu 0.5 Nb 0.5 , that is, the atomic percentage of each alloy element is: Fe75at%, Co10at%, B9at%, P5at%, Cu0.5at%, Nb0.5at%.
[0065] The method for preparing the above-mentioned iron-based amorphous nanocrystalline alloy comprises the following steps:
[0066] (1) High-purity iron, pure cobalt, pure copper, pure niobium, pure boron and Fe-P master alloy are placed in a ceramic crucible according to the designed composition ratio; during the placement process, a layer of iron particle raw material is first placed on the bottom of the crucible, and then other raw materials are placed in sequence, and finally another layer of iron particle raw material is placed to prevent the volatilization of the P element.
[0067] (2) Vacuuming: Place the ceramic crucible in the heating coil, close the furnace door, and pre-vacuum the cavity of the induction melting furnace with a mechanical pump. Use high-purity argon gas for three times. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3 Pa, then turn off the diffusion pump and flush in high-purity argon gas with a pressure of 0.05MPa.
[0068] (3) Using the induction melting method, first adjust the current to 400A, then increase it by 50A for 2 minutes, and then slowly increase the current to about 850A. In order to mix and melt the various components evenly, shake the crucible several times, and keep the molten alloy liquid in a bright red state for 10 minutes. Then reduce the current to 700A and keep it warm for 5 minutes, cast it into a copper mold and cool it for 20 to 30 minutes to obtain an alloy ingot with relatively uniform composition.
[0069] (4) The obtained alloy ingot is used to remove the surface oxide layer with a grinding wheel, and then crushed with a vise. The surface dust and attached oil stains caused by crushing are cleaned with alcohol, and the cleaned crushed master alloy is placed in a quartz tube, and then the quartz tube is placed in the heating coil of the belt-spinning machine. The furnace door is closed and the gas is washed with high-purity argon gas for 3 times. When the cavity is pre-evacuated to below 10Pa with a mechanical pump, high-purity argon gas is then injected to form a protective atmosphere to prevent oxidation. The rotation speed of the copper roller is set to 40m / s, and the pressure difference of the spray casting is set to 0.03MPa. The alloy ingot designed to be distributed is fully melted, and then the molten master alloy liquid is sprayed on the surface of the high-speed rotating copper roller using the pre-set argon pressure difference. The high-speed rotating water-cooled copper roller has a rapid cooling ability, which makes the molten alloy liquid solidify instantly, and an amorphous alloy strip with a width of 1 to 1.5mm and a thickness of 20 to 30um is prepared.
[0070] (5) Cut the amorphous strip into 70 mm pieces and place them in a porcelain boat. Place the porcelain boat in a non-heating zone of a tubular furnace. Evacuate the tubular furnace and introduce nitrogen. Repeat this process 5 times. Finally, maintain a nitrogen atmosphere in the tubular furnace. When the tubular furnace is heated to a predetermined temperature, push the porcelain boat into the heating zone of the tubular furnace and keep the temperature for a predetermined time. In this embodiment, multiple experimental groups are repeated. When the preset temperature is 600°C, the temperature is kept for 60s, 65s, 70s, 75s, and 80s, respectively. When the preset temperature is 650°C, the temperature is kept for 50s, 55s, 60s, 65s, and 80s, respectively. When the preset temperature is 700℃, keep warm for 30s, 35s, 40s, 45s, and 50s respectively; when the preset temperature is 750℃, keep warm for 20s, 25s, 30s, 35s, and 40s respectively; when the preset temperature is 800℃, keep warm for 15s, 20s, 25s, 30s, and 35s respectively; when the preset temperature is 850℃, keep warm for 10s, 15s, 20s, and 25s respectively; when the preset temperature is 900℃, keep warm for 10s, 15s, 20s, and 25s respectively; after keeping warm, quickly push the porcelain boat back to the non-heating area for cooling, and the iron-based amorphous nanocrystalline alloy Fe 75 Co 10 B9P5Cu 0.5 Nb 0.5 .
[0071] Comparative Example 1
[0072] The iron-based amorphous nanocrystalline alloy prepared in Comparative Example 1 is: Fe 85 B5P9Cu 0.5 Nb 0.5 .
[0073] Preparation method of iron-based amorphous nanocrystalline alloy:
[0074] The iron-based amorphous strip prepared in Example 1 was cut into 70 mm lengths, placed in a quartz tube and sealed with a vacuum tube sealer, and then the quartz tube was placed in a tubular annealing furnace heated to a predetermined temperature and kept warm for 10 min. The predetermined temperature was set at the T of the amorphous strip. x1 -T x2 Temperature (T x1 is the crystallization temperature of α-Fe phase, T x2 is the crystallization temperature of Fe-(B, P) phase, α-Fe phase is needed, Fe-(B, P) phase is to be avoided), after insulation, the quartz tube is quickly thrown into a bucket of water for water quenching, and the heat treatment temperatures of different experimental groups are 400℃, 420℃, 440℃, 460℃, 480℃ and 500℃ respectively.
[0075] Comparative Example 2
[0076] The iron-based amorphous nanocrystalline alloy prepared in Comparative Example 2 is: Fe 85 B7P7 0.5 Nb 0.5 .
[0077] Preparation method of iron-based amorphous nanocrystalline alloy:
[0078] The iron-based amorphous strip prepared in Example 2 was cut into 70 mm lengths, placed in a quartz tube and sealed with a vacuum tube sealer, and then the quartz tube was placed in a tubular annealing furnace heated to a predetermined temperature and kept warm for 10 min. The predetermined temperature was set at the T of the amorphous strip. x1 -T x2 Temperature (T x1 is the crystallization temperature of α-Fe phase, T x2 is the crystallization temperature of Fe-(B, P) phase, α-Fe phase is needed, Fe-(B, P) phase is to be avoided). After insulation, the quartz tube is quickly thrown into a bucket of water for water quenching. The heat treatment temperatures of different experimental groups are 400℃, 420℃, 440℃, 460℃, 480℃, 500℃ and 520℃ respectively.
[0079] Comparative Example 3
[0080] The iron-based amorphous nanocrystalline alloy prepared in Comparative Example 3 is: Fe 85 B9P5Cu 0.5 Nb 0.5 .
[0081] Preparation method of iron-based amorphous nanocrystalline alloy:
[0082] The iron-based amorphous strip prepared in Example 3 was cut into 70 mm lengths, placed in a quartz tube and sealed with a vacuum tube sealer, and then the quartz tube was placed in a tubular annealing furnace heated to a predetermined temperature and kept warm for 10 min. The predetermined temperature was set at T x1 -T x2 Temperature (T x1 is the crystallization temperature of α-Fe phase, T x2 is the crystallization temperature of Fe-(B, P) phase, α-Fe phase is needed, Fe-(B, P) phase is to be avoided). After insulation, the quartz tube is quickly thrown into a bucket of water for water quenching. The heat treatment temperatures of different experimental groups are 400℃, 420℃, 440℃, 460℃, 480℃, 500℃ and 520℃ respectively.
[0083] Comparative Example 4
[0084] The iron-based amorphous nanocrystalline alloy prepared in this embodiment is: Fe 80 Co5B9P5Cu 0.5 Nb 0.5 .
[0085] Preparation method of iron-based amorphous nanocrystalline alloy:
[0086] The iron-based amorphous strip prepared in Example 5 was cut into 70 mm lengths, placed in a quartz tube and sealed with a vacuum tube sealer, and then the quartz tube was placed in a tubular annealing furnace heated to a predetermined temperature and kept warm for 10 min. The predetermined temperature was set at the T x1 -T x2 Temperature (T x1 is the crystallization temperature of α-Fe(Co) phase, T x2 is the crystallization temperature of Fe-(B, P) phase, α-Fe phase is needed, Fe-(B, P) phase is to be avoided), after insulation, the quartz tube is quickly thrown into a bucket of water for water quenching, and the heat treatment temperatures of different experimental groups are 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃ and 540℃ respectively.
[0087] Comparative Example 5
[0088] The iron-based amorphous alloy prepared in this embodiment is: Fe 75 Co 10 B9P5Cu 0.5 Nb 0.5 .
[0089] Preparation method of iron-based amorphous nanocrystalline alloy:
[0090] The iron-based amorphous strip prepared in Example 5 was cut into 70 mm lengths, placed in a quartz tube and sealed with a vacuum tube sealer, and then the quartz tube was placed in a tubular annealing furnace heated to a predetermined temperature and kept warm for 10 min. The predetermined temperature was set at the T x1 -T x2 Temperature (T x1 is the crystallization temperature of α-Fe(Co) phase, T x2 is the crystallization temperature of Fe-(B, P) phase, α-Fe phase is needed, Fe-(B, P) phase is to be avoided), after insulation, the quartz tube is quickly thrown into a bucket of water for water quenching, and the heat treatment temperatures of different experimental groups are 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃ and 540℃ respectively.
[0091] The iron-based amorphous nanocrystalline alloys prepared in the above-mentioned embodiments and comparative examples were subjected to saturation magnetic flux density Bs and coercive force Hc measurements. At room temperature, a vibrating sample magnetometer (VSM, Lake Shore 7410) was used to measure the saturation magnetic flux density (Bs) of the alloy strip under an applied magnetic field of 10000 Oe. The coercive force (Hc) was measured under an applied magnetic field of 800 A / m using a soft magnetic DC BH loop analyzer (Linkjoin MATS-2010SD) at room temperature.
[0092] The Bs and Hc of the iron-based amorphous nanocrystalline alloy in each embodiment and comparative example take the optimal values in each experimental group. The test results are shown in Table 1: Sample No. Annealing conditions Chemical formula Bs(T) Hc(A / m) Example 1 800℃-25s <![CDATA[Fe 85 B5P9Cu 0.5 Nb 0.5 ]]> 1.76 1.6 Example 2 800℃-25s <![CDATA[Fe 85 B7P7Cu 0.5 Nb 0.5 ]]> 1.77 2.6 Example 3 800℃-25s <![CDATA[Fe 85 B9P5Cu 0.5 Nb 0.5 ]]> 1.78 3.2 Example 4 700℃-40s <![CDATA[Fe 80 Co5B9P5Cu 0.5 N.b. 0.5 ]]> 1.83 3.4 Example 5 750℃-40s <![CDATA[Fe 75 Co 10 B9P5Cu 0.5 Nb 0.5 ]]> 1.86 5.2 Comparative Example 1 480℃-10min <![CDATA[Fe 85 B5P9Cu 0.5 Nb 0.5 ]]> 1.61 6.3 Comparative Example 2 500℃-10min <![CDATA[Fe 85 B7P7Cu 0.5 Nb 0.5 ]]> 1.62 6.7 Comparative Example 3 500℃-10min <![CDATA[Fe 85 B9P5Cu 0.5 Nb 0.5 ]]> 1.63 11.7 Comparative Example 4 500℃-10min <![CDATA[Fe 80 Co5B9P5Cu 0.5 N.b. 0.5 ]]> 1.74 13.6 Comparative Example 5 520℃-10min <![CDATA[Fe 75 Co 10 B9P5Cu 0.5 Nb 0.5 ]]> 1.76 19.6
[0093] It can be seen from Table 1 above that compared with the typical Finemet alloy (Bs=1.24T, Hc=0.53A / m), the comprehensive performance of the composition of the present invention is greatly improved. For the same component of the iron-based amorphous alloy, the preparation method of the present application is used to prepare the iron-based amorphous nanocrystalline alloy. Compared with the preparation of the iron-based amorphous alloy using the traditional preparation method, the prepared iron-based amorphous nanocrystalline alloy has a higher Bs and a lower Hc.
[0094] The above specific embodiments further elaborate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and should not be regarded as limiting the present invention. Within the spirit and principle of the present invention, any modification, equivalent substitution, improvement, etc. of the embodiments should be included in the protection scope of the present invention.
Claims
1. A method for preparing an iron-based amorphous nanocrystalline alloy, characterized in that: The following steps are included: According to the preset ratio Fe 85-x Co x B 14-y P y Cu 0.5 Nb 0.5 , where 0≤x≤10,4≤y≤10, weigh the iron-based alloy raw material; Induction melting the iron-based alloy raw material to obtain an alloy ingot; The alloy ingot is subjected to strip spinning to prepare an iron-based amorphous alloy strip; The amorphous strip is cut and placed into a porcelain boat; Place the porcelain boat in the non-heating zone of the tube furnace, repeatedly evacuate the tube furnace and introduce nitrogen, and finally maintain a circulating nitrogen atmosphere in the tube furnace; Heat the heating zone of the tube furnace to a preset temperature of 600°C to 900°C; The porcelain boat is pushed into the heating zone of the tube furnace and kept at a preset temperature for different time periods, the holding time being 10s to 80s; then the porcelain boat is quickly pushed back to the non-heating zone for cooling, and the heating zone is at least 1m away from the non-heating zone.
2. The method for preparing an iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: The heat transfer rate is controlled by different heating preset temperatures. When the porcelain boat is pushed into the heating zone, different insulation time periods need to be adjusted. The principle is that the higher the preset temperature, the shorter the insulation time.
3. The method for preparing the iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: Smelting the iron-based alloy raw material to obtain an alloy ingot comprises the following steps: Place a layer of iron granules on the bottom of the crucible, then put other raw materials in order, and place a layer of iron granules on the top. Place the ceramic crucible in the heating coil, close the furnace door, and pre-evacuate the cavity of the induction melting furnace with a mechanical pump. When the vacuum degree reaches below 10Pa, use a diffusion pump to evacuate to 5×10 -3 Pa, then turn off the diffusion pump and inject high-purity argon gas with a pressure of 0.05MPa to form a protective gas atmosphere; When the iron-based alloy raw material is smelted, it is shaken several times and kept warm for a sufficient time to make the alloy liquid more uniform, and then slowly poured into a cooling copper mold to obtain an alloy ingot.
4. The method for preparing the iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: Using the alloy ingot to prepare the iron-based amorphous alloy comprises the following steps: Cut the alloy ingot into pieces, polish the surface oxide skin and transfer it to the polished round nozzle quartz tube, keeping the distance between the copper roller surface and the quartz tube nozzle at 2-3mm; The alloy ingot is heated and melted to form alloy liquid, which is then sprayed onto the surface of a rotating copper roller, so that the alloy liquid is solidified to obtain an iron-based amorphous alloy strip.
5. The method for preparing the iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: The amorphous strip has a width of 1 to 1.5 mm and a thickness of 20 to 30 μm.
6. An iron-based amorphous nanocrystalline alloy, characterized in that: The alloy is prepared by the method for preparing an iron-based amorphous nanocrystalline alloy according to any one of claims 1 to 5.
7. The iron-based amorphous nanocrystalline alloy according to claim 6, characterized in that: Includes materials having the following general chemical formula: Fe 85-x Co x B 14-y P y Cu 0.5 Nb 0.5 , where 0≤x≤10,4≤y≤10.
8. The iron-based amorphous nanocrystalline alloy according to claim 6, characterized in that: The saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy is 1.76T to 1.86T; the coercive force of the iron-based amorphous nanocrystalline alloy is 1.6A / m to 5.2A / m.